Simulation of Temperature Field in Railway Embankment Filling in Seasonal Frozen Areas - Yuan, Ye (International Journal of Mechanical and Electrical Engineering, 2024)
In order to examine the temperature field changes of railway roadbed in seasonal frozen areas under different filling heights, a typical cross-sectional model of Chagan Lake Station railway was established using the finite element numerical simulation software ANSYS. The temperature parameters of the roadbed were calculated based on the atmospheric temperature of local meteorological data, and the temperature fitting curve was used as the temperature boundary condition. Under different filling quantities, the temperature field of the roadbed was simulated for a freeze-thaw cycle, and the temperature curve changes were analyzed. The results indicate that as the filling height increases, the freezing depth line also increases accordingly. When the filling height is 2.5m, the maximum freezing depth at the roadbed is 1.7m. In a freeze-thaw cycle, the freezing process of soil develops from top to bottom, and the melting process develops in two directions: from top to bottom and from a certain depth of soil upwards, with the characteristics of "unidirectional freezing and bidirectional melting". The freezing period starts from early December of each year to the end of March of the following year, and completely melts until the end of April. Melting develops faster than freezing.